2022
DOI: 10.1101/2022.10.20.512999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered infective competence of the human gut microbiome in COVID-19

Abstract: Objectives: Infections with SARS-CoV-2 have a pronounced impact on the gastrointestinal tract and its resident microbiome. Clear differences between severe cases of infection and healthy individuals have been reported, including the loss of commensal taxa. We aimed to understand if microbiome alterations including functional shifts are unique to severe cases or a common effect of COVID-19. Design: We used high-resolution systematic multi-omic analyses to profile the gut microbiome in asymptomatic-to-moderate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…In patients with moderate symptoms, P. veronii was detected in nasopharyngeal samples whereas P. stercorea, B. cellulosilyficus, B. stercoris and P. copri were identified in stool samples. In general, these findings agree with previous studies in COVID-19 patients [81]. Thus, Xu et al found that infected patients showed higher abundance of B. cellulosilyficus [82], whereas B. stercoris and P. copri were associated with ACE2 upregulation and increased proinflammatory cytokine production, respectively, in COVID-19 patients [79,83].…”
Section: Discussionsupporting
confidence: 91%
“…In patients with moderate symptoms, P. veronii was detected in nasopharyngeal samples whereas P. stercorea, B. cellulosilyficus, B. stercoris and P. copri were identified in stool samples. In general, these findings agree with previous studies in COVID-19 patients [81]. Thus, Xu et al found that infected patients showed higher abundance of B. cellulosilyficus [82], whereas B. stercoris and P. copri were associated with ACE2 upregulation and increased proinflammatory cytokine production, respectively, in COVID-19 patients [79,83].…”
Section: Discussionsupporting
confidence: 91%
“…More recently, de Nies et al (2023) applied metagenomics and metatranscriptomics to the stool samples collected from COVID-19 patients and healthy controls and then conducted an integrative analysis with IMP to reveal the effect of the infection on the gut microbiome community and functions. 101 gNOMO. gNOMO is a bioinformatics pipeline specifically designed to process and analyse metagenomics, metatranscriptomics and metaproteomics data in an integrative manner.…”
Section: Integrated Multi-omics Analysis Tools For Microbiome Studiesmentioning
confidence: 99%
“…Notably, alterations in the microbiota persisted long after recovery from the infection. The analyses conducted by de Nies et al (2023) revealed an enrichment of virulence factors and antimicrobial resistance genes in individuals with COVID-19. Notably, these genes were predominantly associated with bacterial families exhibiting heightened abundance during SARS-CoV-2 infection, specifically Acidaminococcaceae and Erysipelatoclostridiaceae .…”
Section: Introductionmentioning
confidence: 99%